Characterization of Salmonella from Three Commercial North Carolina Broiler Farms - Payne, J.B.; Li, X.; Santos, F.B.O.; Sheldon, B.W. (International Journal of Poultry Science, 2006)
Salmonella contamination during the grow-out phase of poultry production is an area that is receiving increased attention. By assessing the relationship of on-farm Salmonella populations to environmental parameters and farm management practices, on-farm pathogen control strategies similar to those developed for processing HACCP programs may be identified. A small survey was conducted to determine Salmonella prevalence, populations, serotypes, and antibiotic resistance in fresh excreta and litter from three North Carolina broiler farms. Litter pH, temperature, ammonia levels, moisture content, and water activity were also measured. Composite litter and fecal samples were aseptically collected from three commercial farms (two houses per site) as a function of bird age (1-3 wks, 4-6 wks) and season (summer, winter) and the population of Salmonella species enumerated using a 3-tube Most Probable Number (MPN) method. Fifty percent of the litter (n = 24) and fecal (n = 24) samples were Salmonella positive. Litter and fecal mean and range of Salmonella populations were 1.70 and < 1.0 to 3.6 and 1.57 and < 1.0 to 3.1 log MPN/g, respectively. A total of four different serotypes were isolated from the six broiler houses with Salmonella Kentucky and Salmonella Heidelberg being the two most common isolates. Ninety-six percent of the isolates were resistant to > 1 antimicrobial agent (s). The results of this limited survey indicate that while Salmonella spp. populations were statistically different due to a three-way interaction of farm, season and flock age, the difference could not be attributed to the main affects.